Improving the Ability to Recognize Consonants Through Smart Box Media for Children aged 4-5 Years in Kindergarten: Peningkatan Kemampuan Mengenal Huruf Konsonan Melalui Media Kotak Pintar Anak Usia 4-5 Tahun Di Taman Kanak-kanak - Nada Bela Untari; Choirun Nisak Aulina (Universitas Muhammadiyah Sidoarjo, 2021)
The ability to recognize consonants has an important role in the lives of early childhood because introducing consonants to children is the first step for children to be able to read and to make a word, consonants and vowels are needed. This study aims to determine the application and results of the